2016
DOI: 10.1002/14651858.cd011420.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Lateral flow urine lipoarabinomannan assay for detecting active tuberculosis in HIV-positive adults

Abstract: BackgroundRapid detection of tuberculosis (TB) among people living with human immunodeficiency virus (HIV) is a global health priority. HIV-associated TB may have different clinical presentations and is challenging to diagnose. Conventional sputum tests have reduced sensitivity in HIV-positive individuals, who have higher rates of extrapulmonary TB compared with HIV-negative individuals. The lateral flow urine lipoarabinomannan assay (LF-LAM) is a new, commercially available point-of-care test that detects lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
118
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 126 publications
(136 citation statements)
references
References 84 publications
5
118
3
Order By: Relevance
“…Interestingly, a study from Shah et al . reported that combining urine LAM assay with Xpert MTB/RIF testing of urine could be an important opportunity to improve the diagnosis of active TB in HIV co‐infected patients, indicating an important use of urine as a specimen type for the diagnosis of HIV‐associated TB.…”
Section: Current Diagnostic Tests In Hiv‐associated Tbmentioning
confidence: 99%
“…Interestingly, a study from Shah et al . reported that combining urine LAM assay with Xpert MTB/RIF testing of urine could be an important opportunity to improve the diagnosis of active TB in HIV co‐infected patients, indicating an important use of urine as a specimen type for the diagnosis of HIV‐associated TB.…”
Section: Current Diagnostic Tests In Hiv‐associated Tbmentioning
confidence: 99%
“…A more recent Cochrane review reported that urine LAM detection by lateral‐flow assays in HIV‐infected TB patients had a median pooled sensitivity range of 29–63% (Shah et al . ). All these variable data highlight the real need for more searches for TB biomarkers and more optimization of test formats.…”
Section: Resultsmentioning
confidence: 97%
“…A meta-analysis in this population reports the LAM used to diagnose TB with a pooled sensitivity of 56% (41–70) and pooled specificity 90% (81–95). Combining Xpert MTB/RIF testing of urine with urine LF-LAM improved overall TB diagnostic sensitivity 75% (61–87) and specificity of 93% (81–97) with the added advantage of Xpert MTB/RIF simultaneously detecting susceptibility to RIF [94]. Peter et al showed that POC LAM reduced mortality at 8 weeks in hospitalised patients [95].…”
Section: Who Endorsed Diagnostic Technologiesmentioning
confidence: 99%